2022
DOI: 10.1515/pm-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Etching of Manganese Aluminum Bronze by Ultrasound in Seawater

Abstract: Manganese Aluminum Bronze (MAB), UNS designation C95700, is an alloy widely used for large marine propellers and other components in hydropower units. MAB has a complex microstructure due to precipitation of intermetallic phases as consequence of the cast process or thermal treatments. When investigating the marine corrosion behavior of MAB alloys, it was found that a metallographic etching attack occurred under the effect of ultrasound, similar to that observed with chemical reagents used for high-alloy bronz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For the use of bronzes in applications where cavitation occurs, it is important to understand the attack of the aqueous medium on the different phases of the microstructure [13]. During cavitation investigations with MAB in seawater, it was found that the microstructure of the bronze was developed by etching [14].…”
Section: Introductionmentioning
confidence: 99%
“…For the use of bronzes in applications where cavitation occurs, it is important to understand the attack of the aqueous medium on the different phases of the microstructure [13]. During cavitation investigations with MAB in seawater, it was found that the microstructure of the bronze was developed by etching [14].…”
Section: Introductionmentioning
confidence: 99%